The Relationship Between Interest Rates and Inflation: Time Series Evidence from Canada - Fazlollahi, Negar; Ebrahimijam, Saeed (Springer Science and Business Media B.V., 2022)
Interest rates play an important role in the monetary policy of countries. This paper examines the interaction between interest rates and macroeconomic factors. The aim of this study is to investigate the existence of a long-run relationship between interest rates and inflation rates to support the Canadian government’s monetary policy of inflation targeting. The obtained empirical results of the study from the time series analysis prove that the Canadian interest rates converge to their long-run equilibrium with 0.031 unit speed of monthly adjustment by the contribution of other Canadian macroeconomic factors. The findings showed that there is bilateral causality between interest rates and inflation rates. Moreover, inflation rates have the largest positive impact on the interest rates of Canada. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.
5th International Conference on Banking and Finance Perspectives, ICBFP 2021 -- 2021-04-20 through 2021-04-22 -- Famagusta -- 277359
Keywords: ARDL error correction method; Granger causality; Maki cointegration; Monetary policy; Zivot and Andrews unit root test